The role of trace elements in Uzbekistan’s vegetation: A biogeochemical analysis - Boymurodova Gulzoda; Tosheva Nurzoda; Ashurova Xurshida (BIO Web of Conferences)
This study examines the biogeochemical role of trace elements in Uzbekistan’s vegetation, focusing on their impact on plant health, growth, and ecosystem stability. By analyzing the distribution and concentration of key trace elements within various plant species and soil types, the research highlights the interactions between these elements and local vegetation. Data collection involved soil and plant sampling across different ecological zones in Uzbekistan, alongside a review of relevant scientific literature. The findings reveal patterns in trace element accumulation and their effects on vegetation, offering insights into environmental health and resource management. This study provides valuable information for environmental scientists, agricultural experts, and policymakers, as it underscores the importance of trace elements in maintaining ecological balance and informs strategies for sustainable land use in Uzbekistan.